The effect of supervised dynamic exercise program on somatosensory temporal discrimination in patients with fibromyalgia syndrome - Zübeyde Tuğçe Korucu; İlknur Onurlu and Alperen Korucu and Zafer Günendi (Archives of Rheumatology, 2021)
Objectives: This study aims to investigate the effect of a supervised dynamic exercise program on somatosensory temporal discrimination (STD) which indicates the central sensory processing ability. Patients and methods: Forty-eight patients (mean age: 43 years; range, 19 to 64 years) with fibromyalgia syndrome (FMS) were included in this prospective, randomized study between April 2018 and October 2018. Demographics and clinical measurements were recorded. The STD threshold was measured by a researcher blinded to the treatment groups. After baseline assessments, the patients were randomized into two groups: the supervised exercise group (SEG) and the home exercise group (HEG) as the control group. The SEG performed submaximal aerobic exercise and low-medium resistant isotonic exercises under the supervision of a physiotherapist, 1-h per day, three days in a week for four weeks. The HEG was given a home-based exercise program consisting of low-to-medium resistance isotonic exercises and aerobic exercises 1-h per day, three days in a week for four weeks. After exercise program, clinical assessments and STD threshold measurement were repeated. Results: Clinical and STD threshold measures improved significantly after four-week exercise program in both groups. The improvements in clinical measures were significantly higher in the SEG. However, there was no difference in the STD threshold improvement between the groups. No correlation was found between the STD threshold measure and clinical features in any patients. Conclusion: Although a significant improvement was achieved in impaired STD threshold with SEG, it was not found to be superior to the amelioration observed with HEG.